PEDF plus DHA modulate inflammation and stimulate nerve regeneration after HSV-1 infection. (August 2017) - He, Jiucheng; Neumann, Donna; Kakazu, Azucena; Pham, Thang Luong; Musarrat, Farhana; Cortina, M. Soledad; Bazan, Haydee E.P.
Abstract: Herpes simplex virus type-1 (HSV-1) infection leads to impaired corneal sensation and, in severe cases, to corneal ulceration, melting and perforation. Here, we explore the potential therapeutic action of pigment epithelial-derived factor (PEDF) plus docosahexaenoic acid (DHA) on corneal inflammation and nerve regeneration following HSV-1 infection. Rabbits inoculated with 100, 000 PFU/eye of HSV-1 strain 17Syn+ were treated with PEDF + DHA or vehicle. PEDF + DHA treatment resulted in a biphasic immune response with stronger infiltration of CD4+T cells, neutrophils and macrophages at 7-days post-treatment (p.t.) that was significantly decreased by 14 days, compared to the vehicle-treated group. Screening of 14 immune-related genes by q-PCR showed that treatment induced higher expression of IFN-γ and CCL20 and inhibition of IL-18 by 7 days in the cornea. PEDF + DHA-treated animals developed less dendritic corneal lesions, opacity and neovascularization. Corneal nerve density increased at 12-weeks p.t. with functional recovery of corneal sensation. Treatment with PEDF + DHA that was postponed by 3 weeks also showed increased nerve density when compared to vehicle. Our data demonstrate that PEDF + DHA promotes resolution of the inflammatory response to the virus and, most importantly, induces regeneration of damaged corneal nerves vital for maintaining ocular surface homeostasis. Highlights: PEDF + DHA treatment to rabbit corneas with acute HSV-1 infection restores sensitivity. The treatment regenerates corneal nerves highly damage by HSV-1 infection. There is a biphasic immune-inflammatory reaction. As a result there is decreased corneal lesions, opacity and neovascularization in treated rabbits.